APAKAH FINANCIAL CONSTRAINT MEMODERASI PENGARUH MODAL KERJA TERHADAP PROFITABILITAS SEBELUM DAN SELAMA PANDEMI COVID 19? - Via Aningtyas Putri; Vega Wafaretta (Jurnal Bisnis dan Akuntansi, 2023)
Working capital decisions are important for financing the operations of manufacturing companies, especially during a pandemic which indicates a decline in working capital. This study aims to examine the effect of working capital (Net Working Capital - NWC) on the profitability of manufacturing companies on the Indonesia Stock Exchange (IDX) during non-pandemic and pandemic conditions covid-19, as well as testing the moderating effect of financial constraint. The sample is determined by technique purposive sampling for manufacturing companies from 2018-2021 and analyzed with moderation regression. Results do not confirm Resource-Based Theory where working capital has a significant negative effect on profitability because high working capital creates additional costs that can reduce profits. In addition, the data shows that each sub-sector has different characteristics in terms of working capital requirements and profit-generating capabilities. There are sub-sectors with low (high) working capital that have high (low) profitability. This negative direction of working capital and profits continued until the pandemic conditions, of course, several sub-sectors experienced a decline in profitability. This study also shows that there is no moderating effect financial constraint, but financial constraint has a significant positive effect on profitability. The lower financial constraint, the company's profits continued to decline which could be due to the company's less than optimal management of available funds. The theoretical and practical implications of this study are unconfirmed Resource-Based Theory due to differences in sub-sector and company characteristics. The results show the importance of management in managing working capital optimally to profitability even in pandemic and financial constraints.